Brazil and Turkey in the 21st century: Strategic interests in comparative perspective1 - da Silva, André Luiz Reis; da Costa, Gabriela Dorneles Ferreira [UNESP] (Pontificia Universidade Catolica de Minas Gerais, 2021)
This research aims to compare the strategic interests and the positioning at the foreign policy level of Brazil and Turkey in the 21st century, considering the rise to power of, respectively, Workers' Party (PT, in Portuguese) and Justice and Development's Party (AKP, in Turkish). Methodologically, it was used bibliographical research and analysis of speeches in the General Debate of the United Nations General Assembly (UNGA) between 2010 and 2015. It was verified convergence between Brazil and Turkey in themes as the acknowledgment of the multipolarity of the World Order, the necessity of the United Nations Security Council (UNSC) reform, the importance of the fortification of the global economic governance by G-20 and the compromise with the International Law, with the terrorism combat and with the Humans Right protections. As divergence point, it was verified the debates about the sort of reform to be implemented at the UNSC and some questions involving the Arab Spring, such as the military intervention at Libya in 2011. At last, some themes are more recurrent at one country's foreign policy than another's; as topics regarding Central Asia and Middle East, at Turkey's case, and subjects regarding BRICS and south-american regional integration, at Brazil's case.
Brasil y Turquía en el siglo XXI: Intereses estratégicos en perspectiva comparada
Brasil e Turquia no século XXI: Interesses estratégicos em perspectiva comparada
Keywords: Brazil; Foreign Policy; Strategic interests; Turkey